Baseline trachoma prevalence in Guinea: Results of national trachoma mapping in 31 health districts. - André Géopogui; Christelly Flore Badila; Mamadou Siradiou Baldé; Cece Nieba; Lamine Lamah; Steven D Reid; Mohamed Lamine Yattara; Jean Jacques Tougoue; Jeremiah Ngondi; Ibrahim Foungotin Bamba; Joseph J Amon; Anthony W Solomon; et al. (Public Library of Science (PLoS), 2018)
BACKGROUND:Based on previous studies, historical records and risk factors, trachoma was suspected to be endemic in 31 health districts (HDs) in Guinea. To facilitate planning for the elimination of trachoma as a public health problem, national trachoma surveys were conducted between 2011 and 2016 to determine the prevalence of trachomatous inflammation-follicular (TF) and trachomatous trichiasis (TT) in all 31 endemic HDs. METHODOLOGY/PRINCIPAL FINDINGS:A total of 27 cross-sectional surveys were conducted, each using two-stage cluster sampling (one survey in 2011 covered five HDs). Children aged 1-9 years and adults aged ≥15 years were examined for TF and TT, respectively, using the World Health Organization (WHO) simplified grading system. Indicators of household access to water, sanitation and hygiene (WASH) were also collected. A total of 100,051 people from 13,725 households of 556 clusters were examined, of whom 44,899 were male and 55,152 were female. 44,209 children aged 1-9-years and 48,745 adults aged ≥15 years were examined. The adjusted prevalence of TF varied between 1.0% (95%CI: 0.6-1.5%) to 41.8% (95%CI: 39.4-44.2%), while the adjusted prevalence of TT ranged from 0.0% (95%CI: 0.0-0.2%) to 2.8% (95%CI: 2.3-3.5%) in the 27 surveys. In all, 18 HDs had a TF prevalence ≥5% in children aged 1-9 years and 21 HDs had a TT prevalence ≥0.2% in adults aged ≥15 years. There were an estimated 32,737 (95% CI: 19,986-57,811) individuals with TT living in surveyed HDs at the time of surveys. CONCLUSIONS/SIGNIFICANCE:Trachoma is a public health problem in Guinea. 18 HDs required intervention with at least one round of mass drug administration and an estimated 32,737 persons required TT surgery in the country. The results provided clear evidence for Guinea to plan for national trachoma elimination.